2006
DOI: 10.1113/jphysiol.2006.110122
|View full text |Cite
|
Sign up to set email alerts
|

Developing a head for energy sensing: AMP‐activated protein kinase as a multifunctional metabolic sensor in the brain

Abstract: The 5 -adenosine monophosphate-activated protein kinase (AMPK) is a metabolic and stress sensor that has been functionally conserved throughout eukaryotic evolution. Activation of the AMPK system by various physiological or pathological stimuli that deplete cellular energy levels promotes activation of energy restorative processes and inhibits energy consumptive processes. AMPK has a prominent role not only as a peripheral sensor of energy balance, but also in the CNS as a multifunctional metabolic sensor. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 78 publications
4
119
0
Order By: Relevance
“…This is the first indication of a tissue-specific function of AMPK in this process and suggests that AMPK may not be as functionally universal in this regard as previously thought. It has been postulated before that AMPK activation in general may have cell-or tissue-specific outcomes (Ramamurthy and Ronnett, 2006). This could be attributable to differential expression and/or activity of its upstream regulators, as well as its downstream effectors mediating such responses.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first indication of a tissue-specific function of AMPK in this process and suggests that AMPK may not be as functionally universal in this regard as previously thought. It has been postulated before that AMPK activation in general may have cell-or tissue-specific outcomes (Ramamurthy and Ronnett, 2006). This could be attributable to differential expression and/or activity of its upstream regulators, as well as its downstream effectors mediating such responses.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular and pharmacological inhibition of NMDA receptors in the hypothalamus is mediated by suppressed AMPK activity and lowers glucose production and increases feeding [101]. Several studies showed that AMPK in the hypothalamus regulates energy metabolism by integrating inputs from hormones, peptides, neurotransmitters, and nutrients [102][103][104]. It is highly likely that glutamate-induced neuronal excitation via NMDA receptors mediates the production of ROS.…”
Section: Pharmacological Aspects Of Redox Regulation In the Feeding Cmentioning
confidence: 99%
“…More recently, it has been suggested that AMPK acts as a general energy sensor and integrator of nutrient and hormonal signals in the CNS (1,12). Hypothalamic AMPKα2 activity is reduced by high glucose levels, the physiological transition from the fasted to the fed state, and by the anorexigenic hormones leptin and insulin (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%